Numerical study of the thermo-energy of a tubular heat exchanger with longitudinal baffles. (2021) - Salhi, Jamal-Eddine; Zarrouk, Tarik; Salhi, Najim
Abstract: The work undertaken in this paper presents a computational study of the flow and heat transfer characteristics in a tubular heat exchanger with longitudinal baffles attached to its inner wall, which is maintained at a constant temperature Tw  = 343 k. This study is carried out for a Reynolds number, Re ranging from 2 × 10 4 to 3 × 10 4, and was devoted first to the case of a smooth tube (without baffles), then to the case of a tube provided with longitudinal baffles of rectangular cross-section, and finally to the case of a tube provided with longitudinal baffles of triangular cross-section. The system of equations governing the thermohydraulic phenomenon consists of the continuity equation (for mass conservation), the Navier-Stokes equations (for momentum conservation), and the first principle equation (for energy conservation). The system of equations thus formulated is a hyperbolic system, which has been solved numerically over the entire domain, using the finite volume approach for its discretization, and the two-equation model (K-ε) for the modeling of turbulence terms. The SIMPLE algorithm is thus used to overcome the problem of velocity–pressure coupling. To meet the needs of aerothermal users. The two fields, thermal and aerodynamic, were analyzed, the friction factor, the Nusselt number, and the thermal efficiency. Finally, the study undertaken was finalized by comparative analysis to identify the relevant parameters in the aerothermal phenomenon and deduce the optimal form to be proposed to aerothermal energy users. The results obtained show that the longitudinal inclusion of the rectangular section baffles improves the thermal performance by 32.37% for the triangular section, and by 44.37% for the case of rectangular section baffles.